How a distance of 10 feet can be fatal - Crandall, William, 1956-; Parnell, John A. (John Alan), 1964-; Spillan, John E. ([London] : SAGE, 2016)
In September 2008 the Little General Store in West Virginia exploded. The findings of investigators revealed a number of areas where poor procedures and lax managing of resources led to the tragedy. This case asks students to think about what steps could be put in place to ensure a similar disaster does not reoccur.
Originally Published in: Crandall, W. R., Parnell, J. A., & Spillan, J. E. (2013). How a Distance of 10 Feet Can Be Fatal. In Crisis management: Leading in the new strategy landscape (2nd ed., pp. 46-50). Los Angeles: SAGE Publications, Inc. ISBN: 9781412991681.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Industrial safety -- Management -- Case studies; Crisis management -- Case studies